2017
DOI: 10.1111/mpp.12572
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously applied dsRNA molecules deriving from the Zucchini yellow mosaic virus (ZYMV) genome move systemically and protect cucurbits against ZYMV

Abstract: Zucchini yellow mosaic virus (ZYMV) causes serious damage in a large number of cucurbits, and control measures are necessary. Transgenic cucurbits expressing parts of the ZYMV genome have been shown to be resistant to the cognate virus. A non-transgenic approach involving the exogenous application of double-stranded RNA (dsRNA) has also been shown to induce resistance in tobacco against Cucumber mosaic virus (CMV) and Tobacco mosaic virus (TMV). In the present study, dsRNA molecules derived from the helper com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 54 publications
7
78
0
1
Order By: Relevance
“…7,8 Some studies have also shown that topically applied dsRNAs can act on both the treated plant area and distal non-treated parts by systemic translocation of dsRNAs via the plant vascular system, following application via mechanical wounding. [9][10][11] These results demonstrate the possibility of active uptake of exogenously applied dsRNAs by plant cells and their processing into siRNAs, which should extend the time of control/prevention against some plant diseases. However, specific features of the target organism (i.e.…”
Section: Rna-based Biocontrol Compounds For External Applicationmentioning
confidence: 75%
See 1 more Smart Citation
“…7,8 Some studies have also shown that topically applied dsRNAs can act on both the treated plant area and distal non-treated parts by systemic translocation of dsRNAs via the plant vascular system, following application via mechanical wounding. [9][10][11] These results demonstrate the possibility of active uptake of exogenously applied dsRNAs by plant cells and their processing into siRNAs, which should extend the time of control/prevention against some plant diseases. However, specific features of the target organism (i.e.…”
Section: Rna-based Biocontrol Compounds For External Applicationmentioning
confidence: 75%
“…Examples include the induction of plant resistance to fungi, insects and viruses following external application of bacterially produced or in vitro synthesized long dsRNAs, hpRNA, or small interfering RNAs (siRNAs) designed to selectively target essential genes of pests and pathogens . Some studies have also shown that topically applied dsRNAs can act on both the treated plant area and distal non‐treated parts by systemic translocation of dsRNAs via the plant vascular system, following application via mechanical wounding . These results demonstrate the possibility of active uptake of exogenously applied dsRNAs by plant cells and their processing into siRNAs, which should extend the time of control/prevention against some plant diseases.…”
Section: Rna‐based Biocontrol Compounds For External Applicationmentioning
confidence: 99%
“…Moreover, they showed that dsRNA levels continuously decreased in the local (treated) tissue from 3 dpi to 9 dpi where dsRNA was no longer detectable (Mitter et al, 2017). More recently, Kaldis et al (2018) showed that exogenously applied dsRNA derived from the silencing suppressor HC-Pro and the coat protein genes of zucchini yellow mosaic virus (ZYMV) protect watermelon and cucumber against ZYMV and spread systemically over long distances in cucurbits (Kaldis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm that AtSRBP1 and AtSRBP4 bind vsiRNA, we next synthesized two ZYMV vsiRNAs, termed vsiRNA21 (21 nt) and vsiRNA22 (22 nt). These specific vsiRNAs were chosen based on their high read counts from an earlier ZYMV study of watermelon plants (Kaldis et al, 2018). Electrophoretic mobility-shift assays (EMSAs) indeed established that both AtSRBP1 and AtSRBP4 bound vsiRNAs ( Figure 6E and Supplemental Figure 5A).…”
Section: Srbps Bind To Viral-derived Srnamentioning
confidence: 97%